IMPROVING EFL STUDENTS’ READING COMPREHENSION AND STUDENTS’ PERCEPTION ON METACOGNITIVE READING STRATEGIES - Linda, Kristina; ., Regina; Sutapa,, Y. Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract The aims of this study were improving EFL students? reading comprehension by using Metacognitive Reading Strategies and finding out the students? perceptions on Metacognitive Reading Strategies. The method of the research was a classroom action research. The research subjects were 29 students majoring in Accounting Program class 3 of Year-10. This research was conducted in three cycles to maximize the students? improvement in comprehending the text. The findings of data collecting revealed that integrating Metacognitive Reading Strategies instruction and raising the students? metacognitive reading strategies awareness have successfully improved the students? reading comprehension. Thus, this study implies that Metacognitive Reading Strategies are needed to be integrated in the teaching and learning reading English in the EFL classroom.   Keywords: Metacognitive Reading Strategies, EFL, reading comprehension Abstrak: Tujuan-tujuan dari penelitian ini adalah meningkatkan pemahaman membaca siswa EFL dengan menggunakan Strategi Membaca Metakognitif dan mengetahui persepsi siswa tentang Strategi Membaca Metakognitif. Penelitian ini adalah sebuah Penelitian Tindakan Kelas. Subjek penelitian adalah 29 siswa Kelas 10 Program Akuntansi 3. Penelitian ini dilakukan dalam 3 siklus untuk memaksimalkan peningkatan pemahaman membaca siswa. Temuan membuktikan bahwa mengintegrasikan pembelajaran Bahasa Inggris dengan Strategi Membaca Metakognitif dan meningkatkan kesadaran Strategi Membaca Metakognitif bagi siswa EFL telah berhasil meningkatkan pemahaman membaca siswa. Demikianlah studi ini menunjukkan bahwa Strategi Membaca Metacognitif perlu untuk diintegrasikan dalam kegiatan mengajar dan belajar bahasa Inggris di kelas EFL. Kata kunci: Strategi Membaca Metakognitif, EFL, Pemahaman Membaca